A controlled trial of a regularly cycled oscillating waterbed and a non-oscillating waterbed in the prevention of apnoea in the preterm infant. Issue 11 (November 1981) - Jones, R A
Abstract : Fourteen preterm infants spent a mean of 23 hours divided into 4-hour periods with and without regular oscillations, 10 infants also being studied for control periods, before and afterwards. Electrocardiogram and impedance pneumogram were recorded continuously and analysed blindly. The waterbed, with or without oscillations, had no effect on apnoea or bradycardia when compared with control periods. Infants had appreciably more episodes of severe bradycardia while on the oscillating than on the non-oscillating waterbed.